2020
DOI: 10.52429/selju.v3i1.359
|View full text |Cite
|
Sign up to set email alerts
|

Instagram Caption As Online Learning Media On The Subject Of Extended Writing During Pandemic Of Covid-19

Abstract: This journal contains Instagram caption as online learning media on the extended writing subject in the midst of Covid-19 pandemic. Instagram is one of the popular culture products in the digital era. It is one of choices to be online learning media especially in improving writing. Most of people have Instagram account in the recent time. They are very active in using Instagram. Anything can be viral on this platform. This study presents the students' perceptions of using social media Instagram. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…It is in line with a previous study that shows Moodle use could improve students' physics conceptual understanding . Besides, several types of research have also shown that the use of innovative and various media increases students' enthusiasm in the learning activity (Bestari et al 2020;Huwaidi et al 2021;Suswanto et al 2021). It is expected to lessen the impact of online learning experienced by the students including the change of sudden learning style caused by the COVID-19 pandemic (Ratu et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It is in line with a previous study that shows Moodle use could improve students' physics conceptual understanding . Besides, several types of research have also shown that the use of innovative and various media increases students' enthusiasm in the learning activity (Bestari et al 2020;Huwaidi et al 2021;Suswanto et al 2021). It is expected to lessen the impact of online learning experienced by the students including the change of sudden learning style caused by the COVID-19 pandemic (Ratu et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…6 out of 11 (55%) articles revealed findings of engagement and 5 out of 11 (45%) articles revealed findings of disengagement. The pieces of evidence of high level of task engagement include indicators such as positive perception of the students towards online classes (Schlenz, Schmidt, Wostmann, Kramer, & Schulz-Weidner, 2020;Hattar et al, 2020;Bestari, Faiza, & Mayekti, 2020), high satisfaction with the course (Khalil et al, 2020) and high scores in online tests . Students also find the task engaging when a novel learning experience is introduced such as the case of using mixed reality modules (Sepasgozar, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This research showed that the students' vocabulary levels increase after they learn writing through Facebook as a social media learning partner (Susilowati, 2019). Bestari and friends used Instagram as a object research focuses in writing and showed that Instagram caption helped students to improved their writing skills (Bestari, 2020). Riana and Testiana focuses their research into speaking skill and they finds the problems of speaking is about difficulties to express their feeling.…”
Section: Introductionmentioning
confidence: 99%